Masculinities and disengagement from jihadi networks: the case of indonesian militant islamists - Duriesmith, David (2022)
Men who join militant Islamist networks often frame their participation in masculine terms, as protectors, warriors or brothers. While the role of masculinities in recruitment to jihadi groups has received increasing attention, their role in disengaging men from armed groups (and particularly men in the global south) have not. This paper explores the role of masculinities in shaping men’s paths out of jihadi networks. Based on life history research with Indonesian former militant Islamist we suggest that men’s pathways out of armed groups are defined by negotiating alternate masculinities, which reposition their gendered role in society from those associated with militancy.